HYDRODYNAMIC FEATURES OF SUSPENSIONS AND EMULSIONS FLOWS - S.R. Rasulov; G.R. Mustafayeva (Academic Scientific Journal of Chemistry, 2021)
This scientific article is devoted to the problems associated with the flow of suspensions and emulsions and some simplifications of the real picture of the flow of a polydisperse medium are made. It is also stipulated that differential equations characterizing the motion of suspensions and emulsions should take into account the fundamental discontinuity of the medium and the physicochemical processes of heat and mass transfer occurring in it. Taking into account all these factors, a general equation for multiphase systems is proposed with certain simplifications that do not change. The behavior of particles in two-phase systems, their concentration, collision and coagulation are considered. As a result, it was concluded that there is a multifactorial interaction and mutual influence of both phases in a dispersed flow. A differential equation of motion of a single i-th spherical particle in suspension was proposed, and an equation describing the drag force of a solid spherical particles. Equations of conservation of mass and momentum are presented for one-dimensional laminar motion of two incompressible phases in a gravity field with the same pressure in the phases. Having studied the parameters of the flow of fine particles in a turbulent gas flow, some assumptions were made. It was found that the pulsating motion of particles, performed by them during one period of gas pulsations, can be represented as a change in the pulsating gas velocity in time. The parameter of entrainment of particles by a pulsating medium is an important characteristic in determining the transport coefficients in a turbulent flow. It is concluded that the presence of various kinds of particles in the liquid complicates the problem of solving hydromechanical problems in turbulent and laminar flow, and the assumptions given in the work facilitate the study of this problem